2003
DOI: 10.1002/chin.200348205
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Natural Products for New Leads as Inhibitors of β‐Amyloid Production: 2‐Hydroxy‐4‐methoxy‐3‐prenyl‐6‐styrylbenzoic Acid from Cajanus cajan

Abstract: isolation and characterization of title compound (I), which is found to inhibit β-amyloid production]. -(RAMAKRISHNA*, N. V. S.; VIJAYAKUMAR, E. K. S.; KULKARNI, A. S.; BHAT, R. G.; PARIKH, S.; DEUSKAR, N.; KALAKOTI, B. S.; Indian J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Sun et al (1995) demonstrated that the preparation of CSA had notable anti-inflammatory property better than salicylic acid. Stilbene extracts that are rich in CSA from pigeonpea have been found to have hypocholesterolemic and hypoglycemic effects for treatment for postmenopausal osteoporosis and they inhibit bamyloid synthesis (Luo et al, 2008;Hoppe, 2002, 2003;Zheng et al, 2007;Ramakrishma et al, 2003). PI has showed many bioactivities such as inhibiting the human placental aromatase, DNA topoisomerase I, decreasing the proliferation of MCF-7 cells, inducing mammalian phase 2 detoxication enzymes, antioxidant enzymes, and anti-Helicobacter pylori activities (Fahey and Stephenson, 2002;Le Bail et al, 2000;Bhamarapravati et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Sun et al (1995) demonstrated that the preparation of CSA had notable anti-inflammatory property better than salicylic acid. Stilbene extracts that are rich in CSA from pigeonpea have been found to have hypocholesterolemic and hypoglycemic effects for treatment for postmenopausal osteoporosis and they inhibit bamyloid synthesis (Luo et al, 2008;Hoppe, 2002, 2003;Zheng et al, 2007;Ramakrishma et al, 2003). PI has showed many bioactivities such as inhibiting the human placental aromatase, DNA topoisomerase I, decreasing the proliferation of MCF-7 cells, inducing mammalian phase 2 detoxication enzymes, antioxidant enzymes, and anti-Helicobacter pylori activities (Fahey and Stephenson, 2002;Le Bail et al, 2000;Bhamarapravati et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Some of these natural products are reported to exhibit tyrosinase inhibitory [2], antibacterial and molluscicidal [3], IkBa kinase inhibitory [4], nematicidal [5], antithrombin [9], and antiplasmodial [10] properties. In the course of our studies of plants from the Madagascar rainforest for cytotoxic natural products, two new cytotoxic alkylene phloroglucinols and one known alkylene resorcinol [11] were isolated after chromatography from the methanolic extract of the dried fruits of Protorhus thouvenotii.…”
mentioning
confidence: 98%
“…Members of the Anacardiaceae family have been shown to contain derivatives of benzaldehyde and phenolic acids [2], [3], [4], and alkyl or alkylene derivatives of catechol, resorcinol, and phenol [5], [6], [7], [8]. Some of these natural products are reported to exhibit tyrosinase inhibitory [2], antibacterial and molluscicidal [3], IkBa kinase inhibitory [4], nematicidal [5], antithrombin [9], and antiplasmodial [10] properties.…”
mentioning
confidence: 99%
“…To overcome these problems, novel nonpeptidic lead structures are of great interest. For several years, there were few structures, usually with an obscure mode of action [11,12] . However, detailed activities were reported by A. Simon for 12 at the Alzheimer/Parkinson conference in Sorrento, March 2005 (IC 50 = 15 n M BACE-1, IC 50 = 230 n M BACE-2, IC 50 = 7,620 n M cathepsin D, T 1/2 ϳ 2.1 h, clearance 76 ml/min/kg, V diss 7.2 l/kg).…”
Section: Introductionmentioning
confidence: 99%